中链甘油三酯对高蔗糖饮食豚鼠在负透镜诱导下近视的保护作用Preventive effect of medium-chain triacylglycerol against negative lens-induced myopia in guinea pigs with high sucrose diet - 陈卓1，石蕊2，谭李玉1，左浩3，王妮3 CHEN Zhuo1, SHI Rui2, TAN Liyu1, ZUO Hao3, WANG Ni3 (Zhongguo youzhi, 2023)
为通过营养学手段防控近视提供参考，研究了中链甘油三酯对高蔗糖饮食豚鼠近视的保护作用。将3周龄豚鼠随机分为中链甘油三酯组（MCT组）、长链甘油三酯组（LCT组）、高蔗糖组（SD组）、正常膳食组（CD组）和对照组（CON组），前三组分别饲喂MCT+高蔗糖饲料、棕榈油+高蔗糖饲料、高蔗糖饲料，CD组和CON组饲喂正常饲料。喂养4周后，分析其屈光度及胰岛素抵抗情况。随后对除对照组外各组豚鼠右眼以负透镜诱导近视造模，左眼作为自身对照。造模5周后测定各组豚鼠的双眼屈光度、胰岛素抵抗水平和血甘油三酯水平。结果表明：高蔗糖饮食各组豚鼠均在4周后出现胰岛素抵抗情况，受负透镜诱导各组豚鼠实验眼在诱导5周后均出现高度近视；高蔗糖饮食各组豚鼠的胰岛素抵抗水平及血甘油三酯水平均高于对照组；高蔗糖饮食各组豚鼠实验眼的近视程度与正常膳食组有显著性差异；MCT组较LCT组和SD组，在胰岛素抵抗水平、右眼受负透镜诱导的近视程度及血甘油三酯水平方面均较低。综上，高蔗糖饮食会使豚鼠产生胰岛素抵抗，加剧负透镜诱导对豚鼠近视性屈光不正的影响，而MCT对高蔗糖饮食加剧的豚鼠受负透镜诱导下的近视有保护作用。In order to provide a reference for the prevention and control of myopia through nutritional means, the protective effect of medium-chain triacylglycerol (MCT) on myopia in guinea pigs with high sucrose diet was investigated. Three-week-old guinea pigs were randomly divided into MCT group, long-chain triacylglycerol (LCT) group, high sucrose (SD) group, normal diet (CD) group and control(CON) group.The first three groups fed with MCT plus high-sucrose feed, olive oil plus high-sucrose feed, simple high-sucrose feed respectively, and the CD and CON groups fed with common feed. After four weeks of feeding, the development of diopters and insulin resistance were analyzed. In the following five weeks, myopia was induced by negative lens in the right eye of each group except the CON group, and the left eye was used as its own control. After five weeks, the changes of binocular diopter and insulin resistance levels of guinea pigs in each group were measured, and the blood triglyceride levels of guinea pigs in each group were also measured. The results showed that all groups on a high-sucrose diet developed insulin resistance after four weeks, and all eyes induced by negative lenses developed high myopia after five weeks of induction. The insulin resistance and blood triglyceride levels were higher in the high-sucrose diet group than in the CON group. The diopter of the experimental eye in the high-sucrose diet group was significantly different from that in the CD group. Compared with the LCT group and SD group, the MCT group was more protected on insulin resistance, negative lens-induced myopia in the right eye, and blood triglyceride levels. In conclusion, a diet with high sucrose can cause insulin resistance in guinea pigs and exacerbate the effect of negative lens induction myopic refractive error in guinea pigs. MCT has a protective effect on lens-induced myopia in guinea pigs exacerbated by high-sucrose diet.